NORMATIVE FRAMEWORK FOR CONTROL AND OPTIMIZATION OF THE PHYSICAL DEVELOPMENT AND SPECIFIC WORKING CAPACITY OF 17-19-YEAR-OLD HANDBALL PLAYERS - Sasho Chanev (Scientific Publishing House. NSA Press, 2021)
The purpose of this study is to reveal the average level and variability of the signs of physical development and specific working capacity of 17-19-year-old Bulgarian handball players and, on this basis, to develop an up-to-date norm framework for control and optimization of sports training in the studied age group. The object of the study is the characteristics of physical development, specific physical fitness, technical and tactical skills, and some mental characteristics. The research was done among 115 handball players between the age of 17 and 19 from the top 10 teams, participating in the national championship for juniors under 19 years old. Anthropometric measurements and sports-pedagogical testing were conducted for the needs of the study with a total of 34 indicators for establishing the level of physical development, specific physical and technical-tactical preparation and some mental characteristics and qualities of the handball players of the studied age group. The following research methods were applied to solve the purpose and tasks of the research: review study and theoretical analysis of the specialized literature, anthropometry, manual dynamometry, sports-pedagogical testing and ascertaining psychological experiment. Frequency analysis and descriptive statistics, sigma estimation method, and index method were used for mathematical-statistical data analysis. The applied approach allowed developing normative tables for evaluation of the results of each competitor or team, based on which, person or team optimization models could be developed, revealing both strengths and weaknesses in their preparation.